2020
DOI: 10.1073/pnas.2009272117
|View full text |Cite
|
Sign up to set email alerts
|

Cavity molecular dynamics simulations of liquid water under vibrational ultrastrong coupling

Abstract: We simulate vibrational strong coupling (VSC) and vibrational ultrastrong coupling (V-USC) for liquid water with classical molecular dynamics simulations. When the cavity modes are resonantly coupled to the O−H stretch mode of liquid water, the infrared spectrum shows asymmetric Rabi splitting. The lower polariton (LP) may be suppressed or enhanced relative to the upper polariton (UP) depending on the frequency of the cavity mode. Moreover, although the static properties and the translational diffusion of wate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
154
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 112 publications
(169 citation statements)
references
References 56 publications
(59 reference statements)
3
154
0
Order By: Relevance
“…[1,2] Under collective VSC,experimental reports indicate not only apeak splitting, i.e., aR abi splitting within molecular infrared (IR) spectroscopy,b ut also the modification of chemical reaction rates [3][4][5][6] and crystallization processes [7] under thermal conditions.A s pioneered first by Ebbesen [3] and co-workers,t hese observations suggest that collective VSC might meaningfully modify individual molecular properties without external pumping-although these intriguing experimental findings cannot yet be well explained by current theory. [8][9][10][11][12][13] As imple example illustrating how conventional theory fails to explain the Ebbesen experiments is to consider the case of N molecules forming VSC with aRabi splitting W N = 2g 0 p N % 100 cm À1 ,w here g 0 denotes the light-matter coupling for individual molecules.B ecause g 0 (= W N /2 p N)i s negligible when N becomes macroscopic, one would guess that individual molecular properties (such as chemical reaction rates) cannot be meaningfully modified by aF abry-PØrot microcavity,atheoretical prediction at odds with several experiments.R ecent efforts [10,14] also suggest that, within aclassical description of cavity photons and molecules, static properties of individual molecules during thermal equilibrium are entirely unchanged under usual VSC setups, indicating an onequilibrium (or perhaps quantum) origin of the Ebbesen experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] Under collective VSC,experimental reports indicate not only apeak splitting, i.e., aR abi splitting within molecular infrared (IR) spectroscopy,b ut also the modification of chemical reaction rates [3][4][5][6] and crystallization processes [7] under thermal conditions.A s pioneered first by Ebbesen [3] and co-workers,t hese observations suggest that collective VSC might meaningfully modify individual molecular properties without external pumping-although these intriguing experimental findings cannot yet be well explained by current theory. [8][9][10][11][12][13] As imple example illustrating how conventional theory fails to explain the Ebbesen experiments is to consider the case of N molecules forming VSC with aRabi splitting W N = 2g 0 p N % 100 cm À1 ,w here g 0 denotes the light-matter coupling for individual molecules.B ecause g 0 (= W N /2 p N)i s negligible when N becomes macroscopic, one would guess that individual molecular properties (such as chemical reaction rates) cannot be meaningfully modified by aF abry-PØrot microcavity,atheoretical prediction at odds with several experiments.R ecent efforts [10,14] also suggest that, within aclassical description of cavity photons and molecules, static properties of individual molecules during thermal equilibrium are entirely unchanged under usual VSC setups, indicating an onequilibrium (or perhaps quantum) origin of the Ebbesen experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Thet heoretical approach we will take is classical cavity molecular dynamics (CavMD) simulations, [14,17] an ewly developed numerical tool implemented by the authors to classically propagate the coupled dynamics between realistic molecules (assumed to stay in their electronic ground-state) and cavity photons in the dipole gauge.S ince the self-dipole term is included in the light-matter Hamiltonian of CavMD simulations,t his numerical approach preserves gauge invariance and maintains numerical stability. [18] Compared with VSC experiments,t his approach has reliably captured many VSC-induced phenomena, including an asymmetric Rabi splitting, [14,19] polariton relaxation to vibrational dark modes on atime scale of ps and sub-ps, [17,20] and adelay of population gain in the singly excited manifold of vibrational dark modes after pumping the lower polariton (LP), ap rocess which stems from polariton enhanced molecular nonlinear absorption. [17,21] Hence,CavMD simulations appears to be apromising tool to study VSC-related phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Because g 0 (=Ω N /2√ N ) is negligible when N becomes macroscopic, one would guess that individual molecular properties (such as chemical reaction rates) cannot be meaningfully modified by a Fabry–Pérot microcavity, a theoretical prediction at odds with several experiments. Recent efforts [10, 14] also suggest that, within a classical description of cavity photons and molecules, static properties of individual molecules during thermal equilibrium are entirely unchanged under usual VSC setups, indicating a nonequilibrium (or perhaps quantum) origin of the Ebbesen experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical approach we will take is classical cavity molecular dynamics (CavMD) simulations, [14, 17] a newly developed numerical tool implemented by the authors to classically propagate the coupled dynamics between realistic molecules (assumed to stay in their electronic ground‐state) and cavity photons in the dipole gauge. Since the self‐dipole term is included in the light‐matter Hamiltonian of CavMD simulations, this numerical approach preserves gauge invariance and maintains numerical stability [18] .…”
Section: Introductionmentioning
confidence: 99%
“…In the last several years, it has been shown that coupling vibrational modes in this way has a pronounced effect on chemistry and molecular properties. [3,[5][6][7][8][9][10][11][12][13][14][15][16][17]20] In this vibrational strong coupling regime (VSC), vibro-polaritonic states (VP + , VPÀ) are formed, separated by the so-called Rabi splitting energy (" h W R ) (Figure 1 a). In typical experiments, a large number N of molecules are coupled by VSC to a single optical mode which leads to the formation of N-1 dark states (DS) which are, together with VP + and VPÀ, delocalized over many molecules.…”
mentioning
confidence: 99%